THE IMPACT OF ACID ACTIVATION PARAMETERS OF DARK BROWN LOAM ON ITS SORPTION PROPERTIES TO CHROMIUM (III) IONS - Бовсуновський, Є.О.; Рябчевський, О.В.; Годовська, Ю.Я.; Личманенко, О.Г. (Proceedings of National Aviation University (archive), 2012)
Today the purification of waste water from heavy metals is an actual environmental problem, which is due to the existence of these different forms of pollution (in the form of salts, oxides etc.). The using of environmentally safe materials can be the direction of solution of this problem. One of them is a common natural sorbent - dark brown loam. Large reserves of this material, cheapness, very high adsorption, ion exchange and filtration properties provide the practical and economic feasibility of its use in the process of purification of waste water from chromium (III) ions. The experimental results on improving of sorption properties of dark brown loam by acid activation of sewage treatment from chromium (III) ions have been presented. The optimal conditions for acid activation of the sorbent, at which provides the maximum degree of purification of water from pollution have been defined. Analysis of researches has confirmed the effectiveness of using dark brown loam, modified by sulfuric acid activation, as the sorbent of chromium (III) ions from waste waters.